Clinico-pathological features of repeat renal biopsies in patients with lupus nephritis at Groote Schuur Hospital, Cape Town - Kajawo, Shepherd (Department of Medicine, 2017)
Background: Repeat renal biopsies in patients with lupus nephritis (LN) are usually done to guide treatment or to establish disease chronicity. Their value is not clear from available literature. There is also no available data in Africa to guide clinicians. Methods: This was a retrospective study of patients undergoing a repeat renal biopsy between January 2003 and December 2014 from a single centre in Cape Town, South Africa. Relevant demographic, clinical and histological records of patients with repeat renal biopsies were documented. Comparison of data from 1st and 2nd renal biopsy was performed. Results: 44 patients had at least 2 biopsies done during the study period. Most patients were females (81.8%). The mean biopsy interval was 2.8± 1.8 (range 0.38 – 9.4) years. Proteinuria was the main indication for the repeat biopsy (36.1%). The glomerular filtration rate and proteinuria worsened between the two biopsies (p=0.001 and 0.019) respectively suggesting disease progression. Most patients (65.4%) with a non-proliferative class of LN at first biopsy progressed into a proliferative class whereas patients with initial proliferative LN at first biopsy (77.8%) remained as proliferative at repeat biopsy. Treatment was changed in 85% of patients at second biopsy. Conclusion: Repeat renal biopsies in patients with LN presents a useful means of assessing disease progression and provides guidance regarding modification of treatment. More studies are however required to evaluate the value of repeat biopsies and perhaps the need for protocol renal biopsies in patients with LN.